Exploring the Role of Internal Control Systems in Financial Statement Quality under Coercive Pressure in Government Entities - Mulyantoro, Cahyo Dwi; Nurkholis, Nurkholis; Atmini, Sari (Journal of Accounting Research, Organization and Economics, 2024)
Objective - This study examines the influence of coercive pressure on financial statement quality and the mediating role of internal control systems in central government accounting entities of ministries/institutions partnering with the State Treasury Service Office of Malang (KPPN Malang).Design/Methodology - The research sample was collected by purposive sampling questionnaire with an 84.38% return rate. It comprised 216 respondents of staff and managers responsible for preparing financial statements in central government work units of ministries/institutions partnering with KPPN Malang. Research data were analyzed using the Partial Least Squares (PLS) technique to predict the relationships between coercive pressure, financial statement quality, and the mediating role of internal control systems.Results - It was found that coercive pressure positively influences financial statement quality. Coercive pressure has a positive effect on internal control systems, and internal control systems have a positive impact on financial statement quality. Meanwhile, internal control systems can mediate the relationship between coercive pressure and financial statement quality.Research limitations/implications - The research findings have practical implications that suggest coercive pressures from stakeholders demanding high-quality financial statements should be responded to by implementing effective internal control systems to ensure the quality of presented financial statements.Novelty/Originality - The novelty of this research lies in examining the mediating role of internal control systems in the relationship between coercive pressure and financial statement quality, which has not been discussed in existing studies.